Multivessel Coronary Artery Disease in Diabetes Mellitus Patients - Mohammed, Amanj Kamal (Kurdistan Journal of Applied Research, 2019)
Coronary artery disease is the most common cardiac disease with a worldwide distribution, and it is responsible for most of the mortalities regarding cardiovascular diseases if not detected early and treated properly. There are many lines in the treatment of coronary artery disease, starting from medical therapy, percutaneous coronary intervention, and coronary artery bypass graft surgery, preference of the choice of the type of the treatment depends on many factors. In fact when coronary artery bypass graft is indicated, although it carries a considerable risk of surgery, but the long-term survival is notably better than the other ways of treatment. This study was done to determine that the prevalence of multivessel coronary artery disease is more in diabetic patients than non-diabetic patients. And more in females than males. In this study hundred, ninety patients were retrospectively studied, all of them underwent coronary artery bypass graft surgery with or without other concomitant cardiac procedures (like valve surgery), but most of them were coronary artery bypass graft alone. We found that the number of coronary arteries affected is strongly related to the presence of diabetes mellitus. And females are more prone to have coronary artery disease than males. Thus diabetes mellitus is the most common risk factor for the development of cardiovascular disease, and the severity of the condition is confirmed by the number of the coronary arteries involved as well as the calcification or multiple stenosis in the same vessel.